2020
DOI: 10.1038/s41467-020-14924-7
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Dzyaloshinskii-Moriya interaction arising from rare-earth orbital magnetism in insulating magnetic oxides

Abstract: The Dzyaloshinskii-Moriya interaction (DMI) is responsible for exotic chiral and topological magnetic states such as spin spirals and skyrmions. DMI manifests at metallic ferromagnet/ heavy-metal interfaces, owing to inversion symmetry breaking and spin-orbit coupling by a heavy metal such as Pt. Moreover, in centrosymmetric magnetic oxides interfaced by Pt, DMI-driven topological spin textures and fast current-driven dynamics have been reported, though the origin of this DMI is unclear. While in metallic syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 44 publications
(63 reference statements)
5
82
2
Order By: Relevance
“…Another important aspect, where in the last 2 years tremendous progress has been made, is the investigation of interfacial DMI and the generation of topological magnetic textures in heterostructures based on MOIs. [155,[239][240][241][242][243] These results promise future progress to be quite similar as in metallic multilayer systems. [56,57,60,[244][245][246][247][248] In this regard, also the development of theoretical concepts explaining the sometimes contradicting experimental results is desirable.…”
Section: Discussionmentioning
confidence: 68%
“…Another important aspect, where in the last 2 years tremendous progress has been made, is the investigation of interfacial DMI and the generation of topological magnetic textures in heterostructures based on MOIs. [155,[239][240][241][242][243] These results promise future progress to be quite similar as in metallic multilayer systems. [56,57,60,[244][245][246][247][248] In this regard, also the development of theoretical concepts explaining the sometimes contradicting experimental results is desirable.…”
Section: Discussionmentioning
confidence: 68%
“…With the advent of vapor‐phase growth methods for preparing thin epitaxial oxide films, including pulsed laser deposition (PLD) and sputtering, thin films of rare earth (RE) iron garnet materials (REIG, formula unit RE 3 Fe 5 O 12 ) have been developed with desirable properties for spintronic applications, including thulium (TmIG), terbium, europium, samarium and other REIG films with perpendicular magnetic anisotropy (PMA). Spin‐orbit torque switching, [ 1,2 ] chiral spin textures, [ 3–5 ] and a relativistic domain wall velocity approaching the magnon group velocity have been reported in Pt/TmIG and Pt/Bi:YIG heterostructures, making these materials promising candidates for memory or logic devices. [ 4–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Spin‐orbit torque switching, [ 1,2 ] chiral spin textures, [ 3–5 ] and a relativistic domain wall velocity approaching the magnon group velocity have been reported in Pt/TmIG and Pt/Bi:YIG heterostructures, making these materials promising candidates for memory or logic devices. [ 4–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…TmIG shows perpendicular magnetization anisotropy (PMA) in a large range of thicknesses from 1.7 nm to at least 15 nm, and, in PMA GGG / TmIG / Pt heterostructures, the robust anomalous Hall effect (AHE) makes it a good candidate to explore the role of SOT at the FMI / HM interface. In addition, it was reported that the DMI in TmIG is of interfacial origin (iDMI) [21,[23][24][25][26], with some reporting that the iDMI originates from the TmIG / HM (e.g Pt) interface [23,24], while others claim that the interface between TmIG and the substrate is responsible for the iDMI [21,25,26], so that the origin of the iDMI is currently being debated. It is thus important to understand the origin of the SOT and the DMI in a substrate / FMI / HM structure, where the SOT and DMI could originate from two different interfaces, as this potentially enables also independent optimization of the DMI and SOT in magnetic insulators.…”
mentioning
confidence: 99%